EVALUASI PEMBELAJARAN BAHASA INDONESIA DI PERGURUAN TINGGI - ARYANIKA, SEPTA (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2015)
Indonesian Language Learning Program Evaluation in higher education aims to measure the achievement of learning implementation program for Indonesian Language subject.The used method is a survey method. The used of instrument are documents, interview and observation guidances. Data is collected for one semester. Based on the phenomenon which is founded in 8 (eight) higher schools in Jakarta, it transpired the following findings as follows: (1) Contex evalution component, (2) Input evaluation component, are founded the facts: (a) The procedur and selection system; (b) Lack of lecturers resources of Indonesian Language subject; (c) the quality of the Indonesian Language lectures; (d) Indonesian Language lecturers have not educational background in Indonesian Language subject; (e) Language lectures have not the academic title as the lecturers; (f) Language Lecturers not obtain the teaching certificate; (g) No standard learning implemenation; (h) Many higher schools have no the required infrastructures; (i) The operational fund of all higher schools is mostly acquired from the students. (3) process evaluation component: (a) Nearly all lecturers met the total of meeting hours; (b) Most of lecturers are on time schedule; (c) Many lecturers have no capability in composing the learning material; (d) No similarity or standarization in delivering the learning material. (4) Product evaluation component are founded that the obtained grade average from the Semester Final Examination in Indonesian Language subject is 86.75 meanwhile the minimum grade is 70 and the maximum grade is 95.